Efektivitas Kerja Karyawan Dalam Penggunaan Kearsipan Elektronik Pada PT. Asabri Kantor Cabang Medan - Reska, Ainun; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This research was conducted to determine the effectiveness of employees' work in the use of the electronic filing system at PT. ASABRI Medan Branch Office. This research was conducted at the office of PT. ASABRI Medan Branch Office which is located at Jl. T. Amir Hamzah No. 4 Helvetia Tim, by taking the research subject are employees who work at PT. ASABRI Medan Branch Office. This research was conducted using a qualitative descriptive method, a research method by collecting actual data, then assembled into an invention or what is commonly called a journal, so that it can provide actual facts about the effectiveness of employees' work in using the electronic filing system at PT. ASABRI Medan Branch Office. The problem to be studied is the archive storage system and work effectiveness. With the results of the study indicate that the employees at PT. ASABRI Kancab Medan has been quite effective in using the existing electronic filing system. Therefore, employees must improve security in electronic archive storage in the company in accordance with the vision that exists at PT. ASABRI Medan Branch Office is to become the best national social insurance management company that is able to provide optimal benefits/guarantees in the implementation of insurance and pension payment activities, as well as the best service for participants while maintaining employee welfare.